Impact of political measures on passenger and freight transport demand in Germany. (October 2020) - Winkler, Christian; Mocanu, Tudor
Highlights: Equal consideration and modelling of passenger and freight transport. Comparison of transport related impacts of three alternative scenarios for Germany. It is necessary to strengthen alternative and sustainable modes of transport to attract more users. Road transport will remain the backbone of the transport system in each scenario. Technological advancements are most important to achieve climate protection goals. Abstract: In this paper we present the findings from the "Transport and Environment" (VEU) project related to the development of transport demand in Germany in three scenarios up to the year 2040. The results were obtained using the German national transport model DEMO, a complex model landscape covering all areas of transport (both passenger and freight), trip purposes and modes. The main findings are expressed in terms of number of trips, mode shares and distance travelled by mode. The results show that it is possible to push the transport sector toward a more sustainable state if comprehensive policy measures are established to reduce road transport and make other modes of transport more attractive. In the Regulated Shift scenario, the distance travelled on the road is 20% lower for passenger transport and 4% lower for freight transport compared to the Reference scenario. However, our results also indicate that road transport will still be the backbone of the future transport system in all scenarios, meaning that the mitigation of the environmental effects is only possible in combination with technological developments of road-based transport systems.